Click train patterns of free-ranging harbour porpoises acquired using T-PODs may be useful as indicators of their behaviour - Koschinski , Sven; Diederichs , Ansgar; Amundin , Mats (J. Cetacean Res. Manage., 2023)
Harbour porpoise signals consist of directional, high frequency stereotypic clicks which can be logged using T-PODs. Variation in interclick intervals (ICIs) can be used to distinguish different acoustic behaviours. So far, studies on ICI variation are mostly descriptive and the behavioural context in which certain click train patterns are emitted is poorly understood. In this study, the behaviour of free-ranging porpoises was quantified by using typical ICI patterns known from the literature. These were recorded using two T-PODs deployed at a wind farm site (Nysted, Denmark) between 14 June and 12 July 2005 and during the entanglement of a porpoise calf in a gillnet (Clayoquot Sound Canada). It was possible to distinguish between feeding, approach behaviour and communication and known ICI patterns associated with these behaviours were used to categorise acoustic data. During feeding typical click trains start with long ICIs (30-70ms) and end with ICIs down to about 2ms. In a transition phase ICIs rapidly decrease. Click trains attributed to feeding were found in the wind farm data at a rate of 6.3d–1 (n=174) with a patchy distribution. We found 20 to 74s long click train sequences with ICIs gradually decreasing from a median of 72ms (range 34 to 143ms) down to 5ms at a rate of 1.6day–1 (n=45). This was interpreted as approach behaviour, in which the animal was acoustically ‘locked on’ to a reflective structure. Communication signals are built up of click trains with very short ICIs (<7.7ms). During the entanglement of a porpoise calf, three different call types were determined at a rate of 8.9min–1 (n=89). One call with variable duration (100 to 890ms) and relatively stable ICIs as low as 3.6ms resembled ‘distress calls’ described by Amundin (1991b). Another call type with durations from 780 to 830ms and ICIs ranging from 3.0 to 10 ms and thus different with respect to ICI curve progression was found only three times. These had a U-shaped ICI curve, similar to an ‘alarm’ or ‘fright’ call described by Busnel and Dziedzic (1966). A third and previously unreported call is characterised by a long call duration (up to 1,270ms) and sometimes oscillating ICIs with an initial decrease from about 9ms to around 7ms and an increase towards the end. The data presented suggest that the T-POD is a promising tool for behavioural studies. It is possible to recognise certain acoustic behavioural categories described in the literature, but it is important to look at the temporal context with other vocalisations in T-POD data, such as ICIs of preceding click trains.